Effect of Oxygen Vacancy on Electrical Property of Acceptor Doped BaTiO3–Na0.5Bi0.5TiO3–Nb2O5 X8R Systems. Issue 9 (6th June 2016) - Sun, Yue; Liu, Hanxing; Hao, Hua; Zhang, Shujun
Abstract : In this study, we reported a new BaTiO3 –Na0.5 Bi0.5 TiO3 –Nb2 O5 –Mn2 O3 /Fe2 O3 /Co3 O4 /In2 O3 X8R system with high dielectric constant (>2100) at room temperature. The impacts of oxygen vacancy ( V O ¨ ) on dielectric, electrical conductivity, and ferroelectric properties were systematically studied. The Curie point is largely depended on the V O ¨ concentration, which can be confirmed by the dielectric behavior and A1g octahedral breathing modes in Raman spectrum. In addition, the activation energy of V O ¨ diffusion is greatly reduced with the increase in V O ¨ concentration. It was found that the remnant polarization and coercive field were both decreased with increasing V O ¨ concentration, due to the facilitated defect dipoles reorientation and domain switching.